Retrofitting Bolted Flange Plate (BFP) Connections Using Haunches and Extended End-Plates - Budi Suswanto; Fikri Ghifari; Yuyun Tajunnisa; Data Iranata (Civil Engineering Journal, 2024)
In Indonesia, one of the most common forms of connection is the Bolted Flange Plate (BFP) moment connection. Nevertheless, their current setups do not satisfy the strict requirements outlined in AISC 358-22. Therefore, this study uses advanced sub-assemblage numerical modeling simulations using ANSYS software to propose a novel way to integrate a half WF extended end-plate connection and trapezoidal haunch in order to fortify BFP moment connections, which does not meet the requirement required by AISC 358-22. Methodologically, the research entails comprehensive modeling and analysis of the proposed retrofit scheme. Six distinct connection models were scrutinized: the BFP-UR representing the existing connection extracted from a structure in Surabaya; the BFP-R4E and BFP-R4ES models, embodying connection retrofits with a half WF extended end-plate; and the BFP-RTR and BFP-RSTR models, embodying connection retrofits with a trapezoidal haunch. Additionally, the BFP-RTRE model integrates both an extended end plate and a trapezoidal haunch in the retrofit scheme. The analytical findings unveil that the proposed strengthening paradigm manifests heightened and superior rotational moment characteristics relative to the pre-reinforcement configuration, albeit encountering stiffness degradation attributable to buckling effects on the main beam. Notably, the analysis indicates that degradation ensues when rotational displacement exceeds 4%, with only the BFP-RTR and BFP-RSTR models exhibiting degradation at a 3% rotation threshold. Crucially, the connections demonstrate the capability to withstand 80% of the beam’s plastic moment under a 4% rotational displacement, thereby aligning with the stringent requisites delineated in AISC 341-22. Doi: 10.28991/CEJ-2024-010-08-03 Full Text: PDF